Rebalancing the Scales: A Comparative Study Between Egyptian Contract Law’s Rules on Unequal Contracts and the American Unconscionability Doctrine - Elnemr, Yousef Samir (AUC Knowledge Fountain, 2024)
Traditionally, contracts were envisioned as pacts struck between equals. Their enforcement was considered a form of honoring the free will and autonomy of the parties. This theoretical imagination is no longer valid today; the concentration of wealth and power in the hands of some individuals or institutions means they can name their terms and force the other party between taking or leaving it. When the need to contract is pressing, the weaker party is forced to accept any imposed terms. Thus, strict enforcement of contractual terms helps the powerful further their interests at the expense of their helpless partners. Today, the law, including Egyptian law, recognizes this situation and intervenes in those unequal contracts to rebalance the scales tipped by inequality. This paper examines the Egyptian Civil Code’s general rules designed to protect weaker contractual parties and suggests reforms to enhance their functionality. It begins by exploring contracts’ source of obligatory power advocating the theory of “Equality in Exchange” which suggests that contract enforceability can only be morally grounded in the fairness of its terms. Next, it presents the relevant rules of the Civil Code and notes the mediocre results of their practical application. Then, an overview of the American doctrine of unconscionability is presented to showcase how the same issues are handled in the legal system of one of the most powerful modern economies. Finally, reforms are suggested to the Egyptian Civil Code to empower courts to protect weaker contractual parties.